Сходство украинских популяций из различных территориальных подразделений по маркерам Y-хромосомы - Утевская, О.М.; Агджоян, А.Т.; Пшеничнов, А.С.; Дибирова, Х.Д.; Чухряева, М.И.; Атраментова, Л.А.; Балановская, Е.В.; Балановский, О.П. (Фактори експериментальної еволюції організмів, 2013)
Aims. To compare the genetic diversity of the Ukrainian regions by the Y-chromosome haplogroups, which are the high effective genetic markers for similar populations. Methods. The genotyping of Y-chromosome markers. Multivariate statistical analysis, correlation analysis. Results. The spectrum and frequency of Y chromosome haplogroups in the Ukrainian populations correspond to the genetic pattern of Eastern Europe. The frequency distribution of Y-chromosome haplogroups in different Ukrainian populations are similar. The genetic similarity of Ukrainian population or difference between them is not determined by the geographical distance. Conclusions. Ukrainian population belonging to different historical and territorial associations are homogeneous for Y-chromosome markers and have a higher genetic similarity to each other than to the neighboring ethnic groups.

Key words: Y-chromosome, haplogroup, Ukrainians, population, gene pool.